Robotics research in Chile: Addressing the needs of the local mining industry at the Advanced Mining Technology Center. (22nd December 2016) - Ruiz-del-Solar, Javier; Vallejos, Paul; Asenjo, Rodrigo; Correa, Mauricio; Parra-Tsunekawa, Isao; Mascaro, Mauricio
The development of research in robotics in a developing country is a challenging task. Factors such as low research funds, low trust from local companies and the government, and a small number of qualified researchers hinder the development of strong, local research groups. In this article, and as a case of study, we present our research group in robotics at the Advanced Mining Technology Center of the Universidad de Chile, and the way in which we have addressed these challenges. In 2008, we decided to focus our research efforts in mining, which is the main industry in Chile. We observed that this industry has needs in terms of safety, productivity, operational continuity, and environmental care. All these needs could be addressed with robotics and automation technology. In a first stage, we concentrate ourselves in building capabilities in field robotics, starting with the automation of a commercial vehicle. An important outcome of this project was the earn of the local mining industry confidence. Then, in a second stage started in 2012, we began working with the local mining industry in technological projects. In this article, we describe three of the technological projects that we have developed with industry support: (i) an autonomous vehicle for mining environments without global positioning system coverage; (ii) the inspection of the irrigation flow in heap leach piles using unmanned aerial vehicles and thermal cameras; and (iii) an enhanced vision system for vehicle teleoperation in adverse climatic conditions.